An Aramaic Ritual for Burning Straw in Sefire IA:36–37 - DeGrado, Jessie (Aramaic studies, 2022)
The Old Aramaic inscription Sefire I (KAI 222) includes, in a series of mimetic curses, a debated clause that has been read by most previous scholars to involve a mysterious {gnbʾ} gannābaʾ(?) ‘thief’, which (or who?) is symbolically burned (Sefire IA:36–37). The present article argues that there are lexicographic (cognates in later Aramaic dialects) and phonological (geminate prenasalization) grounds for understanding {gnbʾ} to encode instead ganbaʾ (< *gabbaʾ) ‘straw’. The burning of this straw to symbolize consequences should a treaty partner renege has clear parallels in Mesopotamian and Syro-Anatolian magical and ritual language, including treaty curses, and produces a more typical image in a list of mimetic curses involving materials (wax), objects (a bow and arrow), and animals (a calf).